PS2-36: Incremental Medical Care Costs of Prostate Cancer for Medicare Beneficiaries - Hornbrook, Mark (Clin Med Res, 2014)
BACKGROUND/AIMS: We estimated incremental monthly medical costs of prostate cancer (PC)–differences in monthly standardized costs between PC cases age = 65 and age-gender-health plan matched cancer-free controls–for SEER-Medicare and HMO Medicare beneficiaries across four 12-month phases of care–Pre-diagnosis, Treatment, Survivorship, End-of-Life–to understand whether type of health care arrangement–FFS indemnity vs. HMO capitation–was associated with differences in PC costs. METHODS: Cases were SEER-Medicare and HMO patients aged = 65 years with PC (per tumor registry). Cancer-free controls were aged male Medicare indemnity beneficiaries and aged male HMO members who had no tumor registry evidence of any cancer prior to 2009. SEER-Medicare controls were a 5% random sample of aged Medicare beneficiaries. HMO controls were frequency matched to cancer cases on a 5:1 ratio by age group, gender, and having health plan eligibility during the year of the diagnosis from the matched prostate cancer case. We used a longitudinal case-control design to estimate incremental medical costs for PC cases starting 12 months prior to diagnosis. We extracted data for 2000–2008 from HMO standardized data warehouses and SEER-Medicare files. We applied Standardized Medicare reimbursement rates to utilization vectors and summed to total monthly medical expenses per patient in 2008 dollars. We analyzed monthly cost trajectories by phase of care and SEER-Medicare vs. HMO for Stages I–III vs. Stage IV vs. unknown Stage cases. RESULTS: Monthly incremental PC costs in the pre-diagnosis phase were negative in the first 3 quarters and then rose rapidly in the quarter prior to diagnosis, with advanced-stage cases showing the steepest. FFS advanced-stage cases had the highest peak costs in the month of diagnosis, followed by HMO advanced stage cases. By the 12th month of the Treatment phase, monthly costs for all study groups converged at about $500 per month. In the first survivorship year, FFA and HMO advanced-stage cases had higher incremental costs than the other study groups. In the last year of life, advanced-stage cases had higher incremental costs than all other groups. CONCLUSIONS: Stage-IV Medicare FFS PC cases received the most costly treatments of all study groups. FFS incremental costs were mostly higher than HMO costs.